If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -1x = -1 Solving -3 + -1x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = -1 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = -1 + 3 -1x = -1 + 3 Combine like terms: -1 + 3 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 3+2x=-11 | | -5x-7=48 | | 1-4x=-11 | | 9(X-2)*2(2X-1)=8 | | 0.3x-0.5(2x+7)=-0.8(x+2) | | 6+9+x=29 | | 4x+1=11x-85 | | 5x^2-30x+225=0 | | 6+7+x=29 | | -8x-12=6x-4(3x-1) | | 2(3x-4)=8(2x+1) | | 11+7+x=35 | | 2X-X=20 | | 4+247=13-5 | | 230-6x=30x+18 | | 9-10=61-38x | | -7(-5p+4a)= | | 3x+4=52 | | 4(x+2)=2(2x+1)+6 | | f(x)=-x^3-2 | | 1.25+6x= | | 6.95-(1.95+0.10x)=0 | | -2(6+9)= | | 5x+11=5x-21 | | 4x^2+(31x)=0 | | 13-(x+8)=6x+2 | | 14.25/5 | | 14.25/4 | | 0.75x+.05(2-x)=10(43) | | -2(x+6)=0,5-14 | | 3x^2=5-2 | | 8399840909205709x=897979070979797009-5 |